Analisis Kepuasan Kerja terhadap Kinerja Karyawan: Studi Kasus pada Indomaret Bandung - Junipriansa, Donni; Handaputra, Muhammad Ivan; Dewantara, Erlangga (ARZUSIN, 2024)
This study aims to analyse the factors that influence job satisfaction and employee performance at Indomaret Sukabirus, Bandung Regency. Using a qualitative approach, data was collected through in-depth interviews with employees from various divisions. The results showed that job satisfaction is influenced by various aspects, including job characteristics, compensation system, career opportunities, supervisory style, and interaction between colleagues. Although salaries have met the Regency Minimum Wage (UMK) standard, dissatisfaction arises due to high workload, limited opportunities for promotion, and suboptimal internal communication. Factors that influence employee performance include the quality of work, quantity, timeliness, efficiency, and the level of independence in carrying out tasks. This study confirms that job satisfaction contributes significantly to improving employee performance, where satisfied employees tend to show higher loyalty and better initiative in carrying out their duties. The findings provide a new perspective on the relationship between job satisfaction and employee performance in the retail industry, and offer strategic recommendations to improve employee well-being and overall organisational efficiency.